ANALYSIS OF ONLINE LEARNING DIFFICULTIES FOR CLASS X STUDENTS ON QUANTUM NUMBERS FOR THE ACADEMIC YEAR 2021/2022 AT MA RAUDHATUSYSYUBBAN - Novi Rahmawanti; Leonye Shafiera Putri; Emilda Prasiska (Sean Institute, 2022)
Since the COVID-19 virus pandemic hit, the learning process has been shifted to online learning. The aim of this research to analysis online learning difficulties to class X MA Raudhatusysyubban year 2021/2022 at quantum number matter in chemistry object. In this paper described difficulties online learning not only from student but also from teacher. The research uses descriptive method. Results of the analysis showed that 26% of students had difficulty answering the test questions on the material of quantum numbers. Students difficulties are not all student’s like chemistry, duration in learning relative short, difficult understand in online learning, application sometimes crashes, internet quota and speed are not enough distube online process and replay learning. Teacher difficulties are each student’s has own internal and external problem, not eazy identify students understanding in online learning include requirement concept before quantum number matter, duration in learning relative short, teacher have to reduce assignments to students, and teacher difficult explain in online learning compared in real classroom.